PENGOLAHAN AIR LINDI DENGAN PROSES BIOFILTER ANAEROB-AEROB DAN DENITRIFIKASI - Said, Nusa Idaman; Hartaja, Dinda Rita Krishumartani (Jurnal Air Indonesia, 2015)
Most of the leachate treatment in Indonesia using pond system, that is maturation ponds, anaerobic ponds, stabilization ponds, and continued using wetland. The weakness of this technology is long retention time (between 30-50 days), thus the building a pond requires a wide area. In addition, the processed leachate is over quality standards to be discharged into the environment agency. To overcome these problems, one alternative is to use a combination of processing leachate within anaerobic-aerobic biofilter and denitrification. The technology is expected to shorten the residence time, so that the land required for the processing of leachate is not too extensive . The processed leachate is also expected to meet the quality standards are allowed to be discharged into the environment. Leachate treatment using anaerobic - aerobic biofilter and the denitrification process with a total hidraulic retention time of 12 day, the retention time in the anaerobic reactor 8 ( eight ) days , the retention time in the aerobic reactor 3 (three) days and retention time in the denitrification reactor 1 (one) day can be generated COD removal efficiency of 97 %, ammonia removal efficiency of 97.56 %, TSS removal efficiency 87.5 % , and nitrate removal efficiency of 86.4 % Keywords : Anaerob-aerob biofilter, denitrification, leachate.